Genomics and proteomics of the liver fluke Opisthorchis felineus - V. A. Mordvinov; N. I. Ershov; O. G. Zaparina; M. Y. Pakharukova (Вавиловский журнал генетики и селекции)
The causative agent of opisthorchiasis, the liver fluke Opisthorchis felineus (Rivolta, 1884) is one of the helminths of humans and animals in Russia. Together with closely related species of trematodes O. viverrini (Poirier, 1886) and Clonorchis sinensis (Loos, 1907), O. felineus is a part of a triad of epidemiologically important trematodes in the family Opisthorchiidae. Adult O. felineus worms infest the hepatobiliary system of warm-blooded animals and might provoke the development of severe pathologies, including malignancy of bile duct epithelium. The high medical importance of O. felineus attracts the attention of researchers. This review briefly summarizes the data about O. felineus genomics and proteomics. The review provides a comparative analysis of the number of genes and sizes of nuclear genomes of a number of flatworms, the distribution of intron lengths, as well as results of synteny between the O. felineus, O. viverrini and C. sinensis genomes. Special attention is paid to a particular form of RNA processing known as trans-splicing, widely presented in the opisthorchiid genomes. We also provide the results of a comparative analysis of the xenobiotic metabolizing system between parasitic and free-living flatworms. Moreover, data on parasitic granulins, which are potential promoters of cholangiocyte neoplasia, are also presented. Data on the O. felineus genomics and proteomics provide first insights into the structural and functional organization of the genome of this parasitic flatworm with a complex life cycle as well as provide a significant contribution to our understanding of “host-parasite” interaction and evolution of this group of parasitic flatworms.